Anti-Atherosclerotic Potential of Phyllanthus emblica Leaf Extract in High-Fat Diet-Induced Mice (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Atherosclerosis is a chronic inflammatory disorder characterized by lipid accumulation and plaque formation within arterial walls, leading to cardiovascular complications. The present study evaluated the anti-atherosclerotic potential of the hydromethanolic leaf extract of Phyllanthus emblica (PHEL) in a high-fat diet (HFD)-induced mouse model. Atherosclerosis was induced by feeding mice an HFD containing 60% calories from fat for 40 days. Animals were divided into four groups: normal control, HFD-induced disease control, PHEL-treated group (400 mg/kg, days 10–40), and atorvastatin-treated group (10 mg/kg, days 10–40). Serum lipid profile, lipoproteins, atherogenic index, inflammatory cytokines, HMG-CoA reductase activity, calcium levels, and vascular biomarkers, including 6-keto-prostaglandin F1α (6-keto-PGF1α) and endothelin-1 (ET-1), were evaluated. The disease control group exhibited dyslipidemia, elevated inflammatory cytokines, altered vascular biomarkers, increased HMG-CoA reductase activity, and arterial mineralization, confirming the development of atherosclerosis. Treatment with PHEL significantly reduced total cholesterol, triglycerides, and low-density lipoprotein levels while increasing high-density lipoprotein concentrations. The extract also significantly decreased the levels of IL-6, IL-18, and TNF-α and restored 6-keto-PGF1α and ET-1 towards normal values, indicating improved vascular function. These findings demonstrate that Phyllanthus emblica leaf extract exerts significant anti-atherosclerotic effects through modulation of lipid metabolism, inflammatory mediators, and vascular biomarkers, suggesting its potential as a promising natural therapeutic agent for the management of atherosclerosis.
Keywords: Phyllanthus emblica; Atherosclerosis; High-fat diet; leaf extract; Dyslipidemia; Inflammatory cytokines; vascular biomarkers; Cardioprotection